The Effect of Enzymatic Modification on the Dyeability of Polyester Fabric with Reactive Dye. Issue 6 (November 2020) - Toprak, Tuba; Anis, Pervin
The inert chemical structure of poly(ethylene) terephthalate (PET) prevents its dyeability with reactive dyes. In this study, the reactive dyeability of polyester fabrics after enzymatic surface modification with different lipases and cutinase was investigated. The reason for the hydrophilicity of the fiber after enzymatic treatment was thought to be functional groups produced after this process, but their peak intensities in Fourier transform infrared spectroscopy (FTIR) were low and shaded by other functional groups. Scanning electron microscopy (SEM) showed that the enzymatic treatment did not cause any surface damage. A slight staining ( K / S = 0.30) of the PET fabrics with the reactive dye occurred after enzymatic treatments. Moreover, the fastness to washing and rubbing of the reactive dye stained fabrics were good to excellent.